Space-time monitoring of coastal pollution in the Gulf of Gaeta, Italy, using δ15N values of Ulva lactuca, landscape hydromorphology, and Bayesian Kriging modelling. (January 2018) - Rossi, Loreto; Calizza, Edoardo; Careddu, Giulio; Rossi, David; Orlandi, Lucia; Jona-Lasinio, Giovanna; Aguzzi, Laura; Costantini, Maria Letizia
Abstract: We investigated the space-time dynamics of N pollution in a Mediterranean gulf (Gulf of Gaeta) by means of δ 15 N variation in seaweed fronds ( Ulva lactuca ) previously collected from an unpolluted habitat. We used a comprehensive deployment grid that enabled the generation of isotopic seascapes (isoseascapes) describing the topography of N pollution in coastal waters and identifying N input hotspots and their pathways of dispersion at sea. The δ 15 N values of U. lactuca increased during 48 h of exposure to the gulf waters, indicating anthropogenic N inputs from wastewater-derived sources. Comparison of the isoseascapes between two years differing in terms of rainfall identified coastal and offshore areas that were vulnerable to freshwater-transported nutrients, consistent with terrestrial hydromorphology and sea surface-water circulation. Isoseacapes were robust enough to reduce deployment effort, representing a powerful tool for monitoring and management strategies and useful for Environmental Protection Agencies, the main target audience of applied ecological research. Highlights: Dynamics of N pollution in Gulf of Gaeta (It) has been studied by δ 15 N in U. lactuca. Isotopic seascapes describe the topography of N pollution in coastal waters. Areas vulnerable to N inputs, consistent with terrestrial hydromorphology, were identified. Isoscapes were robust to reduce deployment effort, representing a powerful tool for sea monitoring.